Factors Predictive of Radiographic Progression in Ankylosing Spondylitis. Issue 2 (4th January 2021) - Sari, Ismail; Lee, Seunghun; Tomlinson, George; Johnson, Sindhu R.; Inman, Robert D.; Haroon, Nigil
Abstract : Objective: Using a longitudinal observational cohort of ankylosing spondylitis (AS) patients, we sought to identify progression rates and factors predictive of spinal progression. As a secondary aim, we analyzed the effect of tumor necrosis factor inhibitor (TNFi) treatment on radiographic progression. Methods: AS patients who had baseline and follow‐up cervical and lumbar radiographs were included in the study. Radiographic damage was assessed by the modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS). A change of 2 mSASSS units in 2 years was defined as progression. The characteristics of the study group such as demographic, clinical, laboratory, and treatment history were collected. Results: There were 350 patients in the study. The mean ± SD mSASSS increased from 9.3 ± 15.8 units at baseline to 17.7 ± 21.7 units by the sixth year. Mean ± SD changes in mSASSS between the years 0 to 2, 2 to 4, and 4 to 6 were 1.23 ± 2.68, 1.47 ± 2.86, and 1.52 ± 3.7 units, respectively. Overall, 24.3% of the group progressed over 2 years. Male sex (hazard ratio [HR] 2.46 [95% confidence interval (95% CI) 1.05, 5.76]), the presence of baseline damage (HR 7.98 [95% CI 3.98, 16]), increased inflammatory markers (log C‐reactive protein level HR 1.35 [95% CI 1.07, 1.70]), and TNFi use (HR 0.82 [95% CI 0.70, 0.96]) were predictive of radiographic progression. There was a 20% reduction in the rate of progression with TNFi. Conclusion: Male sex, the presence of baseline damage, active disease state, and higher inflammatory markers confer a high risk for disease progression. Treatment with TNFi showed a disease‐modifying effect by slowing the rate of radiographic progression.